Stella Bain : a novel - Shreve, Anita (New York : Little, Brown and Company, 2013)
Set against the backdrop of World War I. An American woman, Stella Bain, is found suffering from severe shell shock, surgeon August Bridge and his wife agree to take her in and Bridge quickly develops a clinical interest in his houseguest. Shreve has created a tale about love and the meaning of memory.
Keywords: World War, 1914-1918 -- Fiction; War neuroses -- Fiction; Historical fiction